The Postmodern Turn - Vivian B. Martin (Grounded Theory Review: An International Journal, 2006)
Adherents to classic grounded theory have gotten used to spotting the pretenders working under the grounded theory banner. Some of these fauxGT researchers have worked in a fog, misunderstanding fundamentals of the method; these are the studies that leave us shaking our heads and wondering about the doctoral committee and peer reviewers who did not bother to find out more about the method they were evaluating. More infuriating are the authors who are claiming to improve on grounded theory, to reground it, to quote one notable British author who, lack of hands-on grounded theory experience aside, manages a book-length critique of the method. Two recent books in the “remaking grounded theory” genre are from sociologists with some years of grounded theory projects behind them. Adele E. Clarke, author of Situational Analysis, was a student and colleague of Anselm L. Strauss at the University of California San Francisco. Kathy Charmaz, author of Constructing Grounded Theory, is among the few grounded theorists who studied with Barney G. Glaser and Strauss at UCSF.